2013
DOI: 10.1002/ijc.28497
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of the AZGP1, PIP, S100A8 and UBE2C molecular biomarkers improves outcome prediction in breast carcinoma

Abstract: The deregulation of key cellular pathways is fundamental for the survival and expansion of neoplastic cells, which in turn can have a detrimental effect on patient outcome. To develop effective individualized cancer therapies, we need to have a better understanding of which cellular pathways are perturbed in a genetically defined subgroup of patients. Here, we validate the prognostic value of a 13-marker signature in independent gene expression microarray datasets (n = 1,141) and immunohistochemistry with full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 46 publications
2
50
0
1
Order By: Relevance
“…A growing number of clinical studies suggesting that AZGP1 plays a role in many different cancers [20][21][22] implies that our data might be relevant to the field of oncology. If it is correct that AZGP1 exerts antitumor effects through inhibition of TGFb, 24 AZGP1-deficient mice would be expected to have a higher susceptibility for tumor progression.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A growing number of clinical studies suggesting that AZGP1 plays a role in many different cancers [20][21][22] implies that our data might be relevant to the field of oncology. If it is correct that AZGP1 exerts antitumor effects through inhibition of TGFb, 24 AZGP1-deficient mice would be expected to have a higher susceptibility for tumor progression.…”
Section: Discussionmentioning
confidence: 89%
“…26 Enhanced tumor progression has been shown to correlate with lower expression of epithelial AZGP1. [20][21][22][23] Kong et al 24 found that AZGP1 expression can preserve epithelial integrity by promoting mesenchymal-toepithelial transition in pancreatic cancer cells. Kong et al 24 attributed the prodifferentiation effects of AZGP1 to TGF-b antagonistic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that protein S100-A8 expression levels were significantly associated with the histological type (P= 0.022) and ER positive expression (P=0.009) of breast cancer tumors. Concordantly, Parris et al (33) proposed a combined predictive model for breast cancer outcomes, containing a four-marker panel (α-2-glycoprotein 1, zinc-binding, prolactin-inducible protein, S100-A8 and ubiquitin conjugating enzyme E2 C), which suggested a significant correlation with histological grade, tumor inflammatory cell infiltration, ER and PR status.…”
Section: Cell Motility Locomotionmentioning
confidence: 99%
“…However, protein S100-A8 was also demonstrated to be a marker of poor prognosis for invasive ductal carcinoma of the breast (35). The aforementioned four-marker panel proposed by Parris et al (33) may be used to predict an unfavorable clinical outcome of patients with breast cancer. The present study implemented the Cox proportional hazards model, which demonstrated that protein S100-A8 is not an independent risk factor for prognosis in breast cancer.…”
Section: Cell Motility Locomotionmentioning
confidence: 99%